PENGARUH PEMBERIAN PUPUK BOKASHI FESES KUDA SANDELWOOD TERHADAP NILAI NUTRISI LAMTORO TARAMBA (LEUCAENA LEUCACEPHALA CV. TARRAMBA) - Ferdianus Umbu Lodong; Marselinus Hambakodu (JURNAL PETERNAKAN SABANA, 2022)
This experiment aims to determine the effect of Sandlewood horse faeces bokashi fertilizer on the nutritional value of lamtoro taramba (Leucaena Leucacephala cv. tarramba) plants. This experiment used a completely randomized design (CRD) with 5 treatments and 4 replications namely; P0: without giving Sandlewood horse manure bokashi fertilizer, P1: Sandlewood horse manure bokashi fertilizer 200 grams/planting hole, P2: Sandlewood horse manure bokashi fertilizer 500 grams/per planting hole, P3: Sandlewood horse manure bokashi fertilizer 800 grams/planting hole, P4: Sandlewood horse feces bokashi fertilizer 1000 grams/planting hole. The variables measured were crude fiber and crude protein. The results showed that the treatment had a significat efectct (p<0,050 on crude fiber, but had no significat effect on crude protein. In conclusion, the application of Sandlewood horse feces bokashi fertilizer can produce a low crude fiber content of 7%, and a crude protein content of 25-28%.